(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
The concept of strong β^∗−I− open sets in ideal topological spaces is investigated and some of their properties are obtained, also we study these in relation to some other types of sets. Furthermore, by using the new notion, we define the strong β^∗−I− interior and strong β^∗−I− closure operators.